2003
DOI: 10.1152/japplphysiol.00898.2002
|View full text |Cite
|
Sign up to set email alerts
|

Leg blood flow during submaximal cycle ergometry is not reduced in healthy older normally active men

Abstract: The purpose of the present study was to test the hypothesis that leg blood flow responses during submaximal cycle ergometry are reduced with age in healthy normally active men. Eleven younger (20-25 yr) and eight older (62-73 yr) normotensive, nonendurance-trained men performed both graded and constant-load bouts of leg cycling at the same absolute and relative [% of peak O(2) consumption (Vo(2 peak))] exercise intensities while leg blood flow (femoral vein thermodilution), mean arterial pressure (MAP; radial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 40 publications
10
46
1
Order By: Relevance
“…Although age-related differences between Nl max and PAD can exaggerate differences in perfusion between these 2 groups, studies have demonstrated that active muscle perfusion remains intact in healthy older individuals. 75,76 In all subjects in this protocol, we observed a heterogenous pattern of limb perfusion after exercise consistent with previous investigators. 52,53,77 However, the pattern of perfusion heterogeneity we observed differed among some individuals, suggesting muscle groups being used to perform exercise on the ergometer were inconsistent, and this could have skewed our comparisons.…”
Section: First-pass Contrast-enhanced Calf Muscle Perfusion At Peak Esupporting
confidence: 88%
“…Although age-related differences between Nl max and PAD can exaggerate differences in perfusion between these 2 groups, studies have demonstrated that active muscle perfusion remains intact in healthy older individuals. 75,76 In all subjects in this protocol, we observed a heterogenous pattern of limb perfusion after exercise consistent with previous investigators. 52,53,77 However, the pattern of perfusion heterogeneity we observed differed among some individuals, suggesting muscle groups being used to perform exercise on the ergometer were inconsistent, and this could have skewed our comparisons.…”
Section: First-pass Contrast-enhanced Calf Muscle Perfusion At Peak Esupporting
confidence: 88%
“…While age-related differences between Nl max and PAD could exaggerate differences in perfusion between these two groups, studies have demonstrated that active muscle perfusion remains intact in healthy older individuals (35,36). In all subjects in this protocol, we ob- served a heterogenous pattern of limb perfusion following exercise consistent with previous investigators (14,29,37).…”
Section: Limitationssupporting
confidence: 77%
“…Recently, Donato et al demonstrated that the difference in the leg Q & m response to exercise found between young and old subjects was a product of the response to the exercise stimulus itself, as opposed to variations in resting Q & m between age groups. Collectively, the results of the aforementioned studies are in conflict with other reports where no difference in Q & m was found between young and old subjects during forearm exercise (Jasperse et al, 1994) or dynamic leg exercise (Olive et al, 2002;Proctor et al, 2003b). Specifically, Olive et al (Olive et al, 2002) demonstrated that exercising Q & m is a function of physical activity patterns but not age differences.…”
Section: Aging-induced Alterations In Exercise Hyperemiamentioning
confidence: 71%
“…In that investigation, 1 Hz contractions elicited no consistent increases in arteriolar diameter or V RBC in 24 month-old male Sprague-Dawley rats. In contrast, some studies have found no difference between Q & m to exercising limbs in young and old subjects (Jasperse et al, 1994;Olive et al, 2002;Proctor et al, 2003b). However, the current literature is certainly not definitive on this issue (Wahren et al, 1974;Proctor et al, 1998;Proctor et al, 2003a) with differences possibly related to the activity level of the population studied, the function of the active muscle(s), and/or the intensity of the exercise.…”
Section: Comparisons To Previous Researchmentioning
confidence: 93%